Graphenated carbon nanotubes-based counter electrode for dye-sensitized solar cells - Yusuf, Yusnita (2023)
The counter electrode is one of the most critical components in the dyesensitized solar cell (DSSC). It catalyzes the reduction of iodide/tri-iodide in the electrolyte, bringing the electrons from external loads connected to the cells. A conventional platinum counter electrode is extensively used; however, the concern with platinum-based is that expose to corrosion in an iodine-based electrolyte, which affects the long-term stability of the cell. Therefore, using the carbon-based material to replace the platinum-based in DSSC can address the mentioned problems. This work synthesized a graphenated-carbon nanotube (g- CNT) via the floating-catalyst chemical vapor deposition method. Then, the g- CNT paste was prepared and deposited for the counter electrode. The morphological results revealed that the g-CNT8 obtained 34.5 S/cm, forming a highly conductive network due to graphene foliates at the sidewalls of CNT. This excellent finding is due to the hybrid structure of the g-CNT8, which provides a high defect structure that creates efficient electron transfer in the materials resulting in higher conductivity. For the counter electrode DSSC, briefly, GCC500 film provided good electrical conductivity of 6.28 S/cm. In addition, the GCC500 counter electrode offered excellent catalytic activity for the iodide/triiodide reaction. That is a significant feature in employing counter electrodes to enhance DSSC performance. Furthermore, the DSSC-based GCC500 exhibited 5.68 % of photovoltaic conversion energy, much higher than platinum (3.79 %). Therefore, the GCC500 is an excellent candidate to replace the conventional platinum as a counter electrode in DSSC.